Implications of graphene-based materials in dentistry: present and future - Roma, M.; Hegde, Shreya (Frontiers in Chemistry, 2024)
Since the advent of nanoscience, nanobiomaterials have been applied in the dental industry. Graphene and its derivatives have attracted the most interest of all of them due to their exceptional look, biocompatibility, multiplication differential, and antibacterial capabilities. We outlined the most recent developments about their applications to dentistry in our review. There is discussion of the synthesis processes, architectures, and characteristics of materials based on graphene. The implications of graphene and its counterparts are then meticulously gathered and described. Finally, in an effort to inspire more excellent research, this paper explores the obstacles and potential of graphene-based nanomaterials for dental aspects.